Pendidikan Agama Islam dalam Konteks Multikultural: Strategi Menanamkan Toleransi Sejak Dini - Miftah Kusuma Dewi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Islamic Religious Education (PAI) not only shapes students' faith but also plays a crucial role in instilling an attitude of tolerance in a pluralistic society. In Indonesia's multicultural context, instilling values ​​of tolerance from an early age is an urgent need given the increasing incidence of intolerance, including in educational settings. Studies on the integration of tolerance values ​​into PAI at the early childhood and primary education levels are still limited. Previous research has focused more on secondary and general education, while the role of PAI teachers as agents of religious moderation and the application of experiential learning in early childhood has not been comprehensively studied. This study aims to analyze strategies for integrating tolerance values ​​into PAI learning from early childhood to primary education. Using a descriptive qualitative approach based on literature studies, the discussion focuses on the integration of multicultural values ​​into the PAI curriculum, the role of teachers, and contextual learning methods in developing inclusive character. The results indicate that effective strategies include inclusive curriculum development, experiential learning, teacher role models, and school-family collaboration in fostering a culture of tolerance. Theoretically, this study contributes to formulating a conceptual framework for PAI-based tolerance education that combines multicultural perspectives and religious moderation. Practically, this research offers a learning strategy model that teachers can implement and can serve as a reference for developing a multicultural Islamic Religious Education (PAI) curriculum. Thus, PAI, grounded in the principle of rahmatan lil 'alamin (blessing for the universe), has strategic potential in developing a generation capable of living harmoniously amidst diversity.